A não neutralidade na perspectiva educacional ciência-tecnologia-sociedade - Santos, Rosemar Ayres dos (2012)
The origin of the movement known as Science-Technology-Society (STS), with repercussions in the Science Education, is associated to the questioning of the supposed neutrality of Science & Technology (CT). In Science Education, in the Brazilian context, STS can be considered a growing line of research, in a process of consolidation. However, how the nonneutrality of Science & Technology has been worked, in this line of research, considering the production of knowledge present in Brazilian journals from the area of Science Education? This constitutes the research problem. It is aimed to analyze how the non-neutrality of CT, in the CTS line of research, has been worked on the production of knowledge, present in Brazilian journals in the area of Science Education. As specific objectives: to identify and to characterize the approach given to the dimensions of the non-neutrality of Science- Technology in Brazilian journals, from the area of Science Education; to deep the understanding about the non-neutrality of Science-Technology and to signal referrals for the Science Education, which contribute to the understanding of non- neutrality of Science- Technology, particularly in the field CTS. In terms of theoretical and methodological referrals, consists of qualitative research, bibliographical, being the corpus of analysis constituted from articles presented in three journals published in Brazil, of the area of Science Education. This was submitted to the discursive textual analysis, which consisted of three steps: unitarization, categorization and communication. From the search results, was produced a metatext. The interaction between theoretical and empirical elements resulted in three categories, which summarize the research results: a) the agenda transfers intentions to the scientific-technological product; b) partial understanding of the non-neutrality of CT; and c) the knowledge produced (product) does not is the result only of the traditional epistemic factors: logic + experience.